1995
DOI: 10.1063/1.469638
|View full text |Cite
|
Sign up to set email alerts
|

Potential energy surfaces of C2v and D3h ozone complexes with Li+

Abstract: Articles you may be interested inOn the use of explicitly correlated treatment methods for the generation of accurate polyatomic -He/H2 interaction potential energy surfaces: The case of C3-He complex and generalization J. Chem. Phys. 141, 044308 (2014); 10.1063/1.4890729Ab initio potential energy surface and nearinfrared spectrum of the He-C2H2 complex Energy separation between the open (C 2v ) and closed (D 3h ) forms of ozone Ab initio molecular orbital calculations have been used to study the most importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Otherwise, deficiencies become evident. There have been a small number of studies which employed more appropriate methodologies, e.g., quadratic configuration interaction with single and double excitations (QCISD), coupled-cluster with singles and doubles and linked triples (CCSD(T)), and/or multi-configurational methods, 13,14 but most of these have focused on complexes between O 3 and H 2 O. [15][16][17] Within the experimental context, in their study of the O· · ·O 3 complex through O 3 generation with photolysis of an oxygen matrix at 11 K, Schriver-Mazzuoli et al observed a peak at λ = 360 nm for the photodissociation of the (O 3 ) 2 dimer, but did not provide any structure.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, deficiencies become evident. There have been a small number of studies which employed more appropriate methodologies, e.g., quadratic configuration interaction with single and double excitations (QCISD), coupled-cluster with singles and doubles and linked triples (CCSD(T)), and/or multi-configurational methods, 13,14 but most of these have focused on complexes between O 3 and H 2 O. [15][16][17] Within the experimental context, in their study of the O· · ·O 3 complex through O 3 generation with photolysis of an oxygen matrix at 11 K, Schriver-Mazzuoli et al observed a peak at λ = 360 nm for the photodissociation of the (O 3 ) 2 dimer, but did not provide any structure.…”
Section: Introductionmentioning
confidence: 99%
“…Both KO 2 and KO 3 exist as a triangular C 2 v symmetry structure with the ground spin state as a doublet - 10 (see Figure ). Moreover, Alcami et al have, in a theoretical work, predicted three isomer structures of Li + O 3 that all lie close in energy. In addition to the C 2 v (see structure 2 in Figure ), other isomer structures could exist.…”
Section: Computational Detailsmentioning
confidence: 96%